A study on cyber-attack for IIUM network security practices - Alam, Mohammad Jahedul (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2018)
A cyber security assault is a continuous exploitation of laptop computer systems, technology-structured businesses and networks. Cyber protection assaults use malicious code to change coding system, good judgment or knowledge, leading to tumultuous penalties that can also compromise knowledge and end result in cybercrimes, similar to information and fraud. Cyber safety attack is moreover referred to as an electronic network attack (CNA). Cyber security safety focused on universities, banks and broadcasting firms inside the world per annual. The malware entails in these threats can be delivered down more than one web site and interrupted the system functions by using overwriting the Master Boot Record (MBR) and everyone the logical drives on the hacked servers rendering them unusable. It had been reportable that such a big amount and such a large quantity of computers has been damaged and also the unique quantity of the monetary harm has now not however been calculated in per annul. a lot of serious is that are probable to possess higher damages just in case of happening further attacks, for the reason that unique analysis of motive isn't achieved nonetheless. Nowadays the cyber-attack detection systems are turning into very important and imperative for the infrastructural community security. The stored logs and backup of the information related with the network pastime and the connections related to the community can be used for the detection of a number of kinds of intrusions and malware. Despite the innovation of new technologies of information and communication following the smart security technique of the internet connections and networks, cyber security has becoming the more challenging squad, and research in this field is still in more numerous. Many types of internet tools and technique are invented to fix up the internet security to meet the organizational demand based on modern era's necessity. Considering from all intrusion detection system as researched before for ensuring security for identifying abnormal behaviour or suspicious activities to undermine the legitimate operation of any system. This study examines how the Network management System could aid in the detection of the network attack so that the loses from these could be minimized. The objectives of this study are to design and implementation of a comprehensive architecture of Intrusion Detection System (IDS) in UIA cyber security network. Defense Techniques have been classified in this study and a proposed framework has been implemented to ensure the cyber security in the UIA network system.